Tempos vividos, histórias e memórias construídas: as escolas rurais e suas professoras (Ituiutaba-MG, 1970 a 1990) - Souza, Alciene Muniz de (2021)
This research has as its theme rural schools in the city of Ituiutaba-MG and the performance of their female teachers, in the period from 1970 to 1990.The objectives were: to understand the organization and functioning of rural schools; to apprehend the means by which the female teachers entered teaching in rural schools and to know their practices. In this sense, we tried to answer the following questions: in which social, economic and cultural conditions was rural education carried out in the municipality? How was the initial and in-service training of female teachers working in rural schools? How did these female teachers conduct their practices, considering the lack of pedagogical support and the precarious working conditions? What were the representations produced by the female teachers about the educational, social and cultural roles played in rural schools in the municipality of Ituiutaba, in the Triângulo Mineiro region, and which were the marks that this formation imprinted on their practices?Printed and oral sources were consulted. Among the printed materials are: personal notes, notes, school meeting minutes, legislative minutes, newspapers, reports, class diaries, personal diaries, and fact sheets about the schools. The oral sources were composed of interviews with five female teachers who worked in rural schools. For analysis of the documentation, the following categories were listed: admission of female teachers, practices, working conditions and representations. The results obtained showed that the structure of rural schools implemented in the municipality of Ituiutaba was precarious; the schools were isolated, multigrade and single-teaching, however they were in line with the reality of most rural schools in the whole country. It was found that despite the difficult working conditions, the female teachers played an important role in education, which resulted in the schooling of the children and young people who lived in the rural area. Palavras-chave: Rural schools. Memories. Representations. rural teachers. Ituiutaba.